INTELIGÊNCIA ARTIFICIAL PARA A ADMINISTRAÇÃO PÚBLICA COMO EXPERIÊNCIA PEDAGÓGICA - Martins, A.; Ferreira, J.; Ulpan; Bruno Almeida; Marado, L. (LEARNING ON THE EDGE: BLOCKCHAIN FOR SUPPLY CHAIN MANAGEMENT – A MULTIMETHODOLOGICAL EXPERIENCE, 2023)
Traditionally, pedagogical practices were centred on the teaching perspective, disregarding the learning component. Additionally, each scientific area was mostly focussed on its technical aspects and/or the purity of the concepts very often disregarding the acquisition of practical competencies and the links with other scientific areas. Managing a supply chain successfully requires coordinating and integrating different entities, and visibility is key to that success. Blockchain is a disruptive technology that promotes visibility and overcoming trust issues, but supply chain managers often lack skills in such technologies. This paper aims to describe an innovative pedagogical project developed to promote blockchain hands-on competencies to management students, on the edge between technology and supply chain management, using diverse learning activities. The design of the pedagogical project was based on a combination of teaching methodologies, minimising lectures and enhancing experiential, active and participating methodologies. Several activities were used, from games to simulation of supply dynamics, with and without information, to a hands-on project in which DAML language was used to develop smart contracts to help overcome supply chain management trust challenges. A team of five faculty, all with different backgrounds, including two from the industry, facilitated the learning process by providing continuous feedback to the students during the learning process. The project’s success relied heavily on the preparation of the learning experience. Students were capacitated with management and technological skills in an integrated way. The games and the hands-on project promoted a multidimensional learn-by-doing experience. Additionally, students developed teamwork, oral and critical thinking skills, having to present their final group projects to experts from the industry